Maya, Incas, and Aztecs - Williams, Brian 1943-; Dodds Pennock, Caroline 1978- (New York, New York DK Publishing, 2018)
Presents facts about the Mayan, Incan, and Aztec civilizations, covering daily life, religion, art and technology, and where they are now
"What do you want to find out? Fun facts, amazing pictures, quizzes"--Cover
History
Includes index
Maps on endpapers
1 2 23
Keywords: Aztecs -- Juvenile literature; Aztecs; Incas -- Juvenile literature; Incas; Indians of Central America -- Juvenile literature; Indians of Mexico -- Juvenile literature; Indians of South America -- Juvenile literature; Mayas -- Juvenile literature; Mayas; Aztecs; Incas; Indians of Central America; Indians of Mexico; Indians of South America; Mayas; Instructional and educational works; Juvenile works